Communicating Effectively With People Experiencing Homelessness to Prevent Infectious Diseases . (7th October 2022) - Allen, Elizabeth M; Smither, Betsy; Barranco, Lindsey; Reynolds, Jennifer; Bursey, Kelli; Mattson, Kristin; Mosites, Emily
Abstract: Background: People experiencing homelessness (PEH) are disproportionately affected by many infectious diseases, including coronavirus disease 2019 (COVID-19). However, communication efforts during public health emergencies like the COVID-19 pandemic often do not consider the unique needs of PEH. We examined how PEH seek and receive health information and how traditional health communication methods resonate with them. Methods: We conducted in-person focus groups with PEH in 4 jurisdictions (Cincinnati, Ohio; Denver, Colorado; Sacramento, California; and the Bronx, New York) during July 2021. Results: Findings from 15 focus groups with PEH (n = 53) revealed the need for trusted messengers and consistent messaging across local organizations, as PEH seek to verify information they receive from multiple sources. PEH overwhelmingly preferred to receive health information through face-to-face conversations, especially with healthcare providers with whom they had an established relationship, but they also cited news media, the internet, and social media as their main sources for obtaining health information. PEH reported that effective communication products pair a recommended action with instructions and resources about how to take that action within their community. Conclusions: These findings support healthcare providers collaborating with public health agencies to ensure that infectious disease prevention messages for PEH are provided by trusted messengers, multimodal, paired with resources, and consistent.